Salıva pH, Carıes and OHI-S Score in Stuntıng Pre-School Chıldren in The Swamp Area - Utami, Naning Kisworo; Andrestian, Meilla Dwi; Insana, Aima (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Stunting remains a major global health issue and is associated with impaired physical and cognitive development, as well as increased susceptibility to oral diseases such as dental caries. Environmental factors, including acidic peatland water, may further aggravate oral health conditions among children living in swamp areas. This study aimed to analyze the relationship between salivary pH, dental caries severity (def-t index), and oral hygiene status (OHI-S) in preschool children with stunting living in peatland regions of South Kalimantan, Indonesia. An analytical observational study with a cross-sectional design was conducted involving 32 preschool children aged 2–5 years residing in the working area of the Martapura Timur Public Health Center. Data collection included clinical examination of caries using the WHO criteria, salivary pH measurement with a Krisbow digital pH meter, and assessment of oral hygiene using the Simplified Oral Hygiene Index (OHI-S). Statistical analysis was performed using the Spearman correlation test. The results showed that salivary pH ranged from 5.5 to 7.0, def-t scores ranged from 2 to 8 (mean = 5.34 ± 1.78), and OHI-S scores were 0.00 in 22 children (68.7%) and >0.00 in 10 children (31.3%). A significant association was found between salivary pH and dental caries severity (p = 0.005; α = 0.05), indicating that lower salivary pH is associated with higher caries prevalence. In conclusion, stunted preschool children in peatland areas exhibited acidic salivary conditions and a high caries burden despite relatively good oral hygiene status. These findings highlight the importance of integrating nutritional rehabilitation and oral health education programs to reduce the risk of dental caries in children living in environmentally vulnerable swamp regions.